Foreign direct investment in the development of Vukuvar-Srijem county - Katarina Marošević; Josip Romić (Ekonomski Vjesnik, 2011)
Foreign direct investment (FDI) is a significant source of financing that brings common benefits for the national economy. The benefits resulting from FDI include the transfer of production technology, capacity innovation, improvement of knowledge, skills, organizational and management practices, better access to foreign markets, and acceleration of economic growth. Attracting foreign investment is one of the determinants of the Croatian policy and local authorities in the following period. The aim of this paper is to carry out an analysis of attractiveness of Vukovar-Srijem County for foreign investment and to elaborate on the county’s prospects and potentials. The paper will also discuss the situation and prospects in the county’s environment, as well as identify the activities undertaken by local authorities to encourage and stimulate direct investment.